Awareness of diabetes mellitus among African traditional healers in the Nelson Mandela Metropole - Mea van Huyssteen; Millidhashni Reddy; Nadasen T Naidoo; Shirley-Anne Boschmans; Jane McCartney; Maryna van de Venter (AOSIS, 2004)
Diabetes mellitus, a chronic illness, affects approximately 8% of black South Africans. Traditional healers are an integral part of the lifestyle of the African people. Opsomming Diabetes mellitus, 'n chroniese siekte, affekteer na raming 8% van Suid-Afrika se swart bevolking. Tradisionele genesers is 'n integrale deel van die lewenswyse van dié bevolkingsgroep. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.